Age-related changes in social decision-making: An electrophysiological analysis of unfairness evaluation in the Ultimatum Game. (23rd January 2019) - Fernandes, C.; Gonçalves, A.R.; Pasion, R.; Ferreira-Santos, F.; Barbosa, F.; Martins, I.P.; Marques-Teixeira, J.
Highlights: We examined age differences in the Ultimatum Game performance. We examined age differences in the Medial Frontal Negativity (MFN). Older adults accepted more unfair offers than younger and middle-aged adults. Younger adults had a MFN higher for unfair than for fair offers. Middle-aged and older adults had an MFN similar for fair and unfair offers. Abstract: This study examines age-related differences in behavioral and neural responses to unfairness. Our sample was composed of younger, middle-aged, and older adults, who performed the Ultimatum Game in the proposer role, and in the respondent role during an EEG recording. We administered neurocognitive tests to identify whether patterns in decision-making are associated with age-related changes in cognition. Despite the worse performance in measures of executive functioning, older adults had the best economic strategy by accepting more unfair offers than younger and middle-aged adults. Regarding electrophysiological results, while younger adults showed higher medial frontal negativity (MFN) amplitudes after unfair than after fair offers, middle-aged and older adults had similar amplitudes after both conditions. Our results suggest that aging may be accompanied by an insensitivity to unfairness, which may underlie their higher rates of unfair offers acceptance.